OP07 Analysing intestinal organoids in a multi-omics, systems biology framework to investigate functional processes affected in Crohn's disease due to autophagy impairment. (25th January 2019) - Gul, L; Jones, E; Matthews, Z; Sudhakar, P; Treveil, A; Divekar, D; Buck, J; Jefferson, M; Armstrong, S; Watson, A; Carding, S; Mayer, U; et al.
Abstract: Background: Autophagy is a highly conserved catabolic pathway that eliminates damaged organelles, invading pathogens and specifically degrades proteins. Mutation in autophagy genes and deregulated autophagy are related to various human diseases including Crohn's disease (CD) where autophagy impairment was shown to affect Paneth cells. Previously, we developed the Autophagy Regulatory Network resource (http://autophagyregulation.org ) to better understand the mechanism and regulation of autophagy in disease pathomechanisms. To investigate autophagy-related processes in Paneth cells, we combined ARN with multi-omics data from intestinal organoids. In particular, we investigated how autophagy impairment, often observed in CD, could affect the key cell functions of Paneth cells. Methods: We generated a mouse model lacking Atg16l1 specifically in intestinal epithelial cells making these cells impaired in autophagy. Using a 3D intestinal organoid culture model that we enriched for Paneth cells, we compared the proteomic profiles of organoids derived from the wild-type (WT) and Atg16l1 KO mice. We developed an integrated computational approach combining protein–protein interaction networks, autophagy-targeted proteins and functional information to identify the mechanistic link between autophagy-impairment and disrupted cellular processes. Results: We detected 284 proteins with altered protein levels by comparing the proteomic profiles of organoids derived from normal mice or mice with impaired autophagy. Our integrated analysis—combination of proteomics and network biology approaches—revealed autophagy-mediated mechanisms which degrade essential proteins belonging to key Paneth cell functions such as exocytosis, apoptosis, and DNA damage repair. We performed validation experiments by generating full transcriptomics profiles of both organoid types, and by specifically focussing on Paneth cell-derived lysozyme to confirm our inferred observation of down-regulated exocytosis. Conclusions: We used both experimental and computational approaches to analyse and uncover the systems-level regulation of cellular processes dependent on autophagy in Paneth cells enriched organoids. Strikingly, the analysis revealed that when autophagy is impaired, nearly 300 proteins display increased or decreased abundance, encompassing at least 18 functional processes. Our observations could explain how protein-level alterations in CD as a result of autophagy-impairment could affect Paneth cell functions. The established workflow enables assessing the potential intestinal effect of autophagy-related mutations in CD patients, and prioritise the key affected processes.